L’Analyse du Risque Géopolitique: du Plausible au Probable (Glocalism: Journal of Culture, Politics and Innovation, 2015)
This paper is going to explore the logical process behind risk analysis, particularly in geopolitics. The main goal is to demonstrate the ambiguities behind risk calculation and to highlight the continuum between plausibility and probability in risk analysis. To demonstrate it, the author introduces two notions: the inference of abduction, often neglected in the social sciences literature, and the Bayesian calculation. Inspired by the works of Louise Amoore, this paper tries to go further by studying qualitative tools used in geopolitical risk analysis and establishing links between abduction and Bayesian probability. After a brief exploration of some epistemological contradictions in risk analysis, the paper explores different methodological tools used in geopolitical risk analysis, through a comparison between quantitative and qualitative tools. Finally, the author suggests new avenues for research on risk analysis.
Keywords: risk analysis; geopolitics; abduction; calculation; methodology